Administration of L-type Bovine Spongiform Encephalopathy to Macaques to Evaluate Zoonotic Potential - Imamura, Morikazu; Hagiwara, Ken’ichi; Tobiume, Minoru; Ohno, Minako; Iguchi, Hiromi; Takatsuki, Hanae; Mori, Tsuyoshi; Atarashi, Ryuichiro; Shibata, Hiroaki; Ono, Fumiko (Emerging infectious diseases, 2025)
We administered L-type bovine spongiform encephalopathy prions to macaques to determine their potential for transmission to humans. After 75 months, no clinical symptoms appeared, and prions were undetectable in any tissue by Western blot or immunohistochemistry. Protein misfolding cyclic amplification, however, revealed prions in the nerve and lymphoid tissues.